Kompetensi SDM, Pemanfaatan Teknologi Informasi dan SPIP Terhadap Kualitas Laporan Keuangan Pemerintah Kota Jambi: Komitmen Organisasi sebagai Pemoderasi - Sri Rahayu; Anggun Iga Yuditiya (Jurnal Akuntansi dan Keuangan, 2023)
This study aims to obtain empirical evidence of the influence of human resource competence, utilization of information technology, and internal control systems on the quality of local government financial reports with organizational commitment as a moderating variable. The source of data in research is primary data with a questionnaire. The number of respondents was 67 people. Hypothesis testing uses moderated regression analysis with the help of the SPSS version 23 program. The results show that human resource competence, information technology utilization, and internal control systems affect the quality of the Jambi City government's financial reports. Organizational commitment moderates the influence of human resource competence on the quality of local government financial reports.